SVEP1 as a Genetic Modifier of TEK-Related Primary Congenital Glaucoma - Young, Terri L. (2020)
PURPOSE. Affecting children by age 3, primary congenital glaucoma (PCG) can cause debilitating vision loss by the developmental impairment of aqueous drainage resulting in high intraocular pressure (IOP), globe enlargement, and optic neuropathy. TEK haploinsufficiency accounts for 5% of PCG in diverse populations, with low penetrance explained by variable dysgenesis of Schlemm’s canal (SC) in mice. We report eight families with TEK-related PCG, and provide evidence for SVEP1 as a disease modifier in family 8 with a higher penetrance and severity. METHODS. Exome sequencing identified coding/splice site variants with an allele frequency less than 0.0001 (gnomAD). TEK variant effects were assayed in constructtransfected HEK293 cells via detection of autophosphorylated (active) TEK protein. An enucleated eye from an affected member of family 8 was examined via histology. SVEP1 expression in developing outflow tissues was detected by immunofluorescent staining of 7-day mouse anterior segments. SVEP1 stimulation of TEK expression in human umbilical vascular endothelial cells (HUVECs) was measured by TaqMan quantitative PCR. RESULTS. Heterozygous TEK loss-of-function alleles were identified in eight PCG families, with parent–child disease transmission observed in two pedigrees. Family 8 exhibited greater disease penetrance and severity, histology revealed absence of SC in one eye, and SVEP1:p.R997C was identified in four of the five affected individuals. During SC development, SVEP1 is secreted by surrounding tissues. SVEP1:p.R997C abrogates stimulation of TEK expression by HUVECs. CONCLUSIONS. We provide further evidence for PCG caused by TEK haploinsufficiency, affirm autosomal dominant inheritance in two pedigrees, and propose SVEP1 as a modifier of TEK expression during SC development, affecting disease penetrance and severity.